Education on the dangers of smoking for students of SMP PGRI 1 Ciputat - Mustakim Mustakim; Mizna Sabilla (Universitas Muhammadiyah Magelang, 2022)
Smoking is one of the risky behaviors of adolescents. Various kinds of impacts, especially non-communicable diseases such as stroke, cancer, coronary heart disease, and others can be caused by smoking. This impact is not only for active smokers but also for passive smokers, some of whom do not know the dangers of smoking. The purpose of this service is to provide education regarding the dangers of smoking from an early age and in this case the target is junior high school students. The method used in this service activity is an online discussion using the Whatsup application or better known as kulwap. The activity consisted of filling out the pre-test, delivering the material, and discussing and post-testing. From the results of education, it was found that participants had increased knowledge about smoking and its dangers to health. This is expected to be one of the efforts to prevent adolescents from smoking behavior.